3D Laser Scribed Graphene Derived from Carbon Nanospheres: An Ultrahigh‐Power Electrode for Supercapacitors. Issue 5 (25th January 2019) - Zhang, Wenli; Lei, Yongjiu; Jiang, Qiu; Ming, Fangwang; Costa, Pedro M. F. J.; Alshareef, Husam N.
Abstract: Laser scribed graphene (LSG) electrodes hold great potential as supercapacitor electrodes. However, the rate performance of LSGs has been limited by the micropore‐dominated electrode structure. Here, a new method is proposed to prepare LSG electrodes with a 3D porous framework dominated by meso‐ and macro‐pores, a property that enables exceptional rate performance. The process uses amorphous carbon nanospheres (CNS) as precursors, which, after laser scribing, are transformed into highly turbostratic graphitic carbon electrodes (henceforth denoted as CNS‐LSG) with a 3D framework structure dominated by meso‐ and macro‐pores. When used as electrodes in conventional supercapacitor devices, the CNS‐LSG electrodes exhibit a high volumetric power density of 28 W cm −3, which is 28 times higher than that of current commercial activated carbon supercapacitors, and is the highest among all the reported laser scribed/induced graphene electrodes. Abstract : A sustainable route is developed for the fabrication of 3D laser‐scribed graphene (LSG) from biomasses for high‐power supercapacitor applications. The facile, sustainable fabrication and high power performance of the 3D laser‐scribed graphene electrode enables it to compete with commercial aluminum electrolytic capacitors in a number of applications.